Carnitine Palmitoyltransferase System: A New Target for Anti-Inflammatory and Anticancer Therapy? - Wang, Muyun; Wang, Kun; Liao, Ximing; Hu, Haiyang; Chen, Liangzhi; Meng, Linlin; Gao, Wei; Li, Qiang (Frontiers in Pharmacology, 2021)
Lipid metabolism involves multiple biological processes. As one of the most important lipid metabolic pathways, fatty acid oxidation (FAO) and its key rate-limiting enzyme, the carnitine palmitoyltransferase (CPT) system, regulate host immune responses and thus are of great clinical significance. The effect of the CPT system on different tissues or organs is complex: the deficiency or over-activation of CPT disrupts the immune homeostasis by causing energy metabolism disorder and inflammatory oxidative damage and therefore contributes to the development of various acute and chronic inflammatory disorders and cancer. Accordingly, agonists or antagonists targeting the CPT system may become novel approaches for the treatment of diseases. In this review, we first briefly describe the structure, distribution, and physiological action of the CPT system. We then summarize the pathophysiological role of the CPT system in chronic obstructive pulmonary disease, bronchial asthma, acute lung injury, chronic granulomatous disease, nonalcoholic fatty liver disease, hepatic ischemia–reperfusion injury, kidney fibrosis, acute kidney injury, cardiovascular disorders, and cancer. We are also concerned with the current knowledge in either preclinical or clinical studies of various CPT activators/inhibitors for the management of diseases. These compounds range from traditional Chinese medicines to novel nanodevices. Although great efforts have been made in studying the different kinds of CPT agonists/antagonists, only a few pharmaceuticals have been applied for clinical uses. Nevertheless, research on CPT activation or inhibition highlights the pharmacological modulation of CPT-dependent FAO, especially on different CPT isoforms, as a promising anti-inflammatory/antitumor therapeutic strategy for numerous disorders.